If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4 + -8k) + -1 = -61 (4 * 3 + -8k * 3) + -1 = -61 (12 + -24k) + -1 = -61 Reorder the terms: 12 + -1 + -24k = -61 Combine like terms: 12 + -1 = 11 11 + -24k = -61 Solving 11 + -24k = -61 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -24k = -61 + -11 Combine like terms: 11 + -11 = 0 0 + -24k = -61 + -11 -24k = -61 + -11 Combine like terms: -61 + -11 = -72 -24k = -72 Divide each side by '-24'. k = 3 Simplifying k = 3
| 40q^2-40q-30=0 | | 1/4h-8= | | 37+x=-2(1-7x) | | 3x+7y=176 | | -4k-44k=36 | | .05x+15=y | | (a-7)(2a+9)= | | 1u^2-4u-45=0 | | 2x^2+102=-60 | | 3X+4=22whatisX | | 10r=90 | | U^2-4u-45=0 | | -8(-2+2x)+8=-40 | | 72=4y+12 | | f(x)=-0.0009x^2+0.2088x | | 6h+13=5 | | m+123+29=180 | | -3-(-56)= | | -d^2+d=-6 | | f=3(22) | | -2+2.3w=10 | | 4(a+3)=6a+12 | | m+123+23=180 | | 12x+11+-4= | | 266=-7(-7x+11) | | x+15=7x-9 | | 4n=944 | | 4=x/13+1 | | 7x+3y=37 | | 4a+3=6a+12 | | 23=-1+6(3x-2) | | 7n-4n+11n= |